Turning carbon fiber into a stress-sensitive composite material. Issue 27 (22nd June 2016) - Villani, M.; Delmonte, D.; Culiolo, M.; Calestani, D.; Coppedè, N.; Solzi, M.; Marchini, L.; Bercella, R.; Zappettini, A.
Abstract : Carbon fiber-based piezoelectric transducer by ZnO nanorods functionalization. Abstract : A piezoelectric investigation of a nano-engineered transducer consisting of zinc oxide nanorods grown in situ on carbon fibers has been performed by means of dynamic hysteresis and capacitance measurements. The device has been stimulated using both static and dynamic stress: the occurrence of characteristic current vs. voltage polarization lobes of a ferroelectric material (stressed piezoelectric) and the corresponding saturation polarization of 290 μC cm −1 (at 2.4 V μm −1 electric field) have been recorded under static stress application. Under dynamic stress conditions a 400% capacitance increase has been measured with respect to the unstressed device. It is noteworthy that these results have been achieved using the carbon fiber itself as conductive element, without the need for external wiring, providing a true integration of the piezoelectric transducer into carbon fiber based materials. The presented nano-engineered device acts as stress sensor and can actively react to the applied stress to hinder the deformation, enabling the design of smart carbon fiber based composites.